High VISTA expression is linked to a potent epithelial-mesenchymal transition and is positively correlated with PD1 in breast cancer - Rezouki, Ibtissam; Zohair, Basma; Ssi, Saadia Ait; Karkouri, Mehdi; Razzouki, Ibtissam; Elkarroumi, Mohamed; Badou, Abdallah (Frontiers in Oncology, 2023)
Breast cancer is the most common type of tumor in women worldwide. Immune checkpoint inhibitors, particularly anti-PDL1, have shown promise as a therapeutic approach for managing this disease. However, this type of immunotherapy still fails to work for some patients, leading researchers to explore alternative immune checkpoint targets. The Ig suppressor of T cell activation domain V (VISTA) has emerged as a novel immune checkpoint that delivers inhibitory signals to T cells and has demonstrated encouraging results in various cancers. Our study investigated the association of VISTA expression with clinicopathological parameters in breast cancer patients, its involvement in the Epithelial-Mesenchymal-Transition (EMT) process, and its correlation with PD1 expression. Transcriptomic analysis revealed that VISTA was associated with lobular and metaplastic histological type, tumor size, lymph node status, ER and PR negative status, and the TNBC molecular subtype. Furthermore, VISTA expression was strongly associated with an immunosuppressive tumor microenvironment. Immunohistochemistry analysis corroborated the transcriptomic results, indicating that VISTA was expressed in most immune cells (94%) and was significantly expressed in breast cancer tumor cells compared to matched adjacent tissues. Our study also showed for the first time that VISTA overexpression in breast cancer cells could be associated with the EMT process. Additionally, we identified a positive correlation between VISTA and PD-1 expression. Together, these results highlight the immunosuppressive effect of VISTA in breast cancer patients and suggest that bi-specific targeting of VISTA and PD-1 in combination therapy could be beneficial for these patients.